2019
DOI: 10.1177/0300060519865633
|View full text |Cite
|
Sign up to set email alerts
|

Association between asymptomatic sexually transmitted infections and high-risk human papillomavirus in cervical lesions

Abstract: ObjectiveThis study aimed to determine the association of asymptomatic sexually transmitted infections (STIs), including Ureaplasma urealyticum (UU), Mycoplasma hominis (MH), Mycoplasma genitalium, Chlamydia trachomatis, and herpes simplex virus type 2, with high-risk human papillomavirus (hrHPV) in cervical intraepithelial lesions and neoplasms.MethodsA total of 320 hrHPV-positive and 160 hrHPV-negative women were divided into high-grade squamous intraepithelial lesion (HSIL) + invasive cervical cancer and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Previously published studies have in fact reported a high prevalence of the HPV 51 genotype in Italian women [15,18,19]. The high prevalence of HPV 16 is in keeping with the worldwide spread of this genotype, not only among women but also in the male population [6,9,14,20,21].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Previously published studies have in fact reported a high prevalence of the HPV 51 genotype in Italian women [15,18,19]. The high prevalence of HPV 16 is in keeping with the worldwide spread of this genotype, not only among women but also in the male population [6,9,14,20,21].…”
Section: Discussionmentioning
confidence: 77%
“…There is growing evidence on the role of other Sexually Transmitted Infections (STIs) as co-factors for the development of cervical cancer in HPV-positive women [8,9]. Interactions between HPV and other pathogens that share similar mucosal sites could accelerate cancer progression, enhancing HPV replication and infection persistence.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated the potential role of sexually transmitted infections (STIs) in the development of cervical cancer in HPV-positive women [ 7 ]. Interactions between high-risk HPV (hrHPV) infections and other pathogens could accelerate cancer progression, enhancing HPV replication and persistence of infection.…”
Section: Introductionmentioning
confidence: 99%
“…A high prevalence of STIs has also recently been reported in Italy in association with hrHPV and cervical dysplasia [ 8 ]. Wang and colleagues reported an association between Ureaplasma urealyticum (UU) subtypes and cervical cancer [ 7 ]; further studies reported that Chlamydia trachomatis (CT) increases the risk of cervical cancer [ 9 , 10 ]. Multiple STIs are therefore believed to represent a risk factor for cervical cancer [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Possible synergistic effects also existed between CT, Uup3, Uup6, and Mh infections and HR-HPV infection ( Table III ). CT, Uup3, Uup6, and Mh likely contribute to HPV infection ( 25 ), which was different from the species that contributed to CIN progression. Combined with the results presented in Table IV , we note that it is not the exact same species of pathogen with that in Table III , that could promote CIN progression though mostly similar.…”
Section: Discussionmentioning
confidence: 99%